Survival of patients living with HIV and cancer in Cali, Colombia (Colombia Medica, 2023)
Background:People living with HIV have an increased risk of cancer compared to the general population. However, with the increase in life expectancy and advances in antiretroviral therapy, the survival of patients with cancer and HIV has changed.Objective:To determine the survival of patients living with HIV and cancer in Cali, Colombia.Methods:A retrospective cohort study was conducted at the Fundación Valle del Lili, Cali, Colombia. Data from the HIV database was crossed with data from the hospital and population-based cancer registries between 2011 and 2019. Patients